Development of articulate storyline 3 learning multimedia on students’ cognitive learning outcomes in green chemistry material in sustainable development 2030 for grade X students at MA Negeri Sidenreng Rappang - Alfiyyah Nurhafanah; Handy Ferdiansyah; Hasanuddin B; Zulkifli N (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to develop Articulate Storyline 3 learning multimedia to improve students’ cognitive learning outcomes in Green Chemistry material within the context of Sustainable Development 2030 for Grade X students at MA Negeri Sidenreng Rappang. The background of this study is based on the need for interactive digital learning media that can increase students’ attention, participation, and understanding of chemistry concepts, especially materials that require contextual and visual explanations. This research employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The data were collected through observation, interviews, documentation, questionnaires, and learning outcome tests. The developed product was validated by media and material experts to determine its validity, while practicality was assessed through teacher and student responses. The effectiveness of the multimedia was examined by comparing students’ cognitive learning outcomes before and after using the media. The developed multimedia integrates text, images, audio, video, interactive quizzes, navigation buttons, and automatic feedback to support independent and active learning. This study is expected to produce learning multimedia that is valid, practical, and effective for chemistry learning, particularly in helping students understand the concept of Green Chemistry and its relevance to sustainable development goals. Therefore, Articulate Storyline 3-based multimedia can be used as an innovative alternative learning medium to support technology-based learning in senior high school chemistry classes.